Association of adverse cardiovascular events with gabapentin and pregabalin among patients with fibromyalgia. - Yiheng Pan; Robert P Blankfield; David C Kaelber; Rong Xu (PLoS ONE, 2024)
Objective Fibromyalgia, a chronic pain disorder, impacts approximately 2% of adults in the US. Gabapentin and pregabalin are common treatments to manage fibromyalgia-related pain. Our recent study showed the risk of adverse cardiovascular events increased in diabetic neuropathy patients who were prescribed gabapentin or pregabalin. Here, we investigated whether the prescription of gabapentin or pregabalin has similar cardiovascular risk in patients with fibromyalgia. Methods This retrospective cohort study leveraged electronic health records from 64 US healthcare organizations with 112 million patients. The study population included 105,602 patients first diagnosed with fibromyalgia and followed by a prescription of gabapentin, pregabalin, or other FDA-approved drugs for treating fibromyalgia from 2010 to 2019. Outcomes were deep venous thrombosis (DVT), myocardial infarcts (MI), peripheral vascular disease (PVD), strokes, heart failure, and pulmonary embolism (PE). In propensity-score-matched cohorts, 1-year and 5-year hazard ratios (HRs) were computed with their respective 95% confidence intervals (CIs). Additionally, we conducted sensitivity analyses on the subpopulations without other possible indications. Results For 5-year follow-up, gabapentin increased the risk of PVD (HR = 1.46, 95% CI = 1.17-1.80), MI (HR = 1.31, 95% CI = 1.03-1.66), heart failure (HR = 1.27, 95% CI = 1.10-1.48), DVT (HR = 1.80, 95% CI = 1.33-2.44), and PE (HR = 2.23, 95% CI = 1.62-3.07). Pregabalin increased the risk of DVT (HR = 1.49, 95% CI = 1.01-2.20), and PE (HR = 2.24, 95% CI = 1.43-3.50). For 1-year follow-up, gabapentin increased the risk of PVD (HR = 1.32, 95% CI = 1.11-1.57), DVT (HR = 1.35, 95% CI = 1.09-1.68), and PE (HR = 1.36, 95% CI = 1.17-1.57). Pregabalin increased the risk of PVD (HR = 1.32, 95% CI = 1.06-1.63) and PE (HR = 1.25, 95% CI = 1.03-1.52). Sensitivity analyses showed similar trends. Conclusion In fibromyalgia patients, the prescription of gabapentin and pregabalin moderately increased the risk of several adverse cardiovascular events. This risk, together with benefits and other adverse reactions, should be considered when prescribing these medications for fibromyalgia patients.